2009
DOI: 10.1111/j.1095-8312.2009.01329.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ecophenotypic trends within three European freshwater mussel species (Bivalvia: Unionoida) using traditional and modern morphometric techniques

Abstract: Most species of freshwater mussels (Unionoida) show a wide variability in shell form and size but an understanding of which factors determine unionoid morphology is poor. We identified ecophenotypic trends in shell and internal characters within three unionoid species from two habitat types (marinas and river) of the River Thames, UK, using traditional and modern morphometric techniques. In marinas, all species grew to larger maximum sizes than in the river, which might be a result of higher temperatures and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 37 publications
4
69
0
2
Order By: Relevance
“…Several studies proved that many animal populations have various ecophenotypic individuals (Langerhans et al, 2003;Zieritz and Aldridge, 2009). Therefore, morphological variations in giant gourami strains from Sumatera and Kalimantan can be referred as to different ecophenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies proved that many animal populations have various ecophenotypic individuals (Langerhans et al, 2003;Zieritz and Aldridge, 2009). Therefore, morphological variations in giant gourami strains from Sumatera and Kalimantan can be referred as to different ecophenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the factors causing it and regardless of its adaptive significance, it seems to be a good indicator of mussels' microhabitats. For example, in Unio pictorum (Linnaeus, 1758) inhabiting a large lowland river, the Thames, Zieritz et al (2009Zieritz et al ( , 2010 found similar differences in shell morphology between sampled microhabitats (marina vs. river channel).…”
Section: Dorsal Archingmentioning
confidence: 95%
“…One reason for larger arching of the shell may be exposure of the posterior part of the shell to water current, which may physically cause twisting the shell towards the bottom due to distortion of the shell-secreting mantle margin (Zieritz & Aldridge, 2009). Regardless of the factors causing it and regardless of its adaptive significance, it seems to be a good indicator of mussels' microhabitats.…”
Section: Dorsal Archingmentioning
confidence: 99%
“…The effect of water flow on shell morphology of freshwater molluscs was mostly assessed as significant (Baker 1928;Shileyko 1967;Lam and Calow 1988;Zieritz and Aldridge 2009). In my study, the water flow proved to be the only hydrological factor to influence appreciably the shell morphology in both morphotypes though the external differences between snails living in lotic and lentic habitats could not be perceived without statistical means.…”
mentioning
confidence: 56%